2010
DOI: 10.1021/jm901633v
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptidic Tetrafluorophenoxymethyl Ketone Cruzain Inhibitors as Promising New Leads for Chagas Disease Chemotherapy

Abstract: A century after discovering that the Trypanosoma cruzi parasite is the etiological agent of Chagas disease, treatment is still plagued by limited efficacy, toxicity, and the emergence of drug resistance. The development of inhibitors of the major T. cruzi cysteine protease, cruzain, has been demonstrated to be a promising drug discovery avenue for this neglected disease. Here we establish that a nonpeptidic tetrafluorophenoxymethyl ketone cruzain inhibitor substantially ameliorates symptoms of acute Chagas dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 54 publications
3
68
1
7
Order By: Relevance
“…In particular, prototype K777 (also known as K11777) has been efficacious in preclinical models of T. cruzi infection, including immunocompetant and immunodeficient mice (20,21) and dogs (22). An ␣-ketone irreversible cruzipain inhibitor has also recently shown efficacy in a murine model (23). These studies show the potential of cruzipain inhibitors as anti-T. cruzi therapies.…”
mentioning
confidence: 94%
“…In particular, prototype K777 (also known as K11777) has been efficacious in preclinical models of T. cruzi infection, including immunocompetant and immunodeficient mice (20,21) and dogs (22). An ␣-ketone irreversible cruzipain inhibitor has also recently shown efficacy in a murine model (23). These studies show the potential of cruzipain inhibitors as anti-T. cruzi therapies.…”
mentioning
confidence: 94%
“…Despite the majority of prior inhibitor development for cruzain has focused on the S1′, S1, and S2 pockets, inhibitors with changes focusing S3 pockets showed a potential inhibition. Because the S3 pocket of cruzain to be large and open-ended, unlike others cysteine proteases as cathepsin S 45 wich normally displays a small and well-defined S3 subsite, studies also showed heterocycles were chosen with potential for hydrophobic interactions with the hydrophobic side of the pocket and with potential for hydrogen-bonding interactions with the serine residue in the S3 pocket 46 and the ring C of fukugetin performs this role mentioned above. Cruzain also substitutes Tyr61 and Tyr67 for the smaller side chains of Ser and Leu, respectively, changing the contacts with the P3 side chain.…”
Section: Discussionmentioning
confidence: 99%
“…Among peptidyl inhibitors, the irreversible inhibitor, N-acylhydrazone has been studied (Ifa, 2000;dos Santos Filho, 2009), as well as the halomethyl ketone based (Ashall, 1990;Harth, 1993), diazomethane ketones (Shaw, 1994;Lalmanach, 1996), vinyl sulfones (Roush, 2001;Engel, 1998;Barr, 2005;Jacobsen, 2000), and reversible inhibitors such as oxadiazoles (Ferreira,2009), and aryl ureas (Du, 2000). In the non-peptidyl group thiosemicarbazones (Du, 2002), triazole, triazine nitriles (Brak, 2010;Mott, 2010) and non-peptidic vinylsulfones ) can be found some of which are presented in Table 4. Among all chemical classes of inhibitors of cruzipain (Cz) researched until now, vinyl sulfone can be highlighted as it is in an advanced stage clinical trial.…”
Section: Peptidasesmentioning
confidence: 99%